Ms. Mentor's impeccable advice for women in academia - Toth, Emily (Book collections on Project MUSE., 1997)
In question-and-answer form, Ms. Mentor advises academic women about issues they daren't discuss openly, such as: How does one really clamber onto the tenure track when the job market is so nasty, brutish, and small? Is there such a thing as the perfectly marketable dissertation topic? How does a meek young woman become a tiger of an authority figure in the classroom-and get stupendous teaching evaluations? How does one cope with sexual harassment, grandiosity, and bizarre behavior from entrenched colleagues?Ms. Mentor's readers will find answers to the secret queries they were afraid to ask anyone else. They'll discover what it really takes to get tenure; what to wear to academic occasions; when to snicker, when to hide, what to eat, and when to sue. They'll find out how to get firmly planted in the rich red earth of tenure. They'll learn why lunch is the most important meal of the day.